Microglia-Specific Expression of HEXA and HEXB Leads to Poor Prognosis in Glioblastoma Patients - Jia, Mengxian; Zhang, Wenbin; Zhu, Junle; Huang, Changgang; Zhou, Jian; Lian, Jiashu; Wang, Ying; Teng, Honglin; Huang, Zhihui (Frontiers in Oncology, 2021)
Glioblastoma multiforme (GBM) is one of the deadliest cancers in brain. There have been few treatment advances for GBM despite increasing scientific understanding of this disease. β-hexosaminidase (Hex) is an important enzyme system in human body, encoded by two genes, HEXA and HEXB, are closely related to central nervous system (CNS) diseases such as Sandhoff disease (SD) and Tay-Sachs disease (TSD). However, the expression pattern and function of HEXA and HEXB in GBM remains unclear. Here, we found that both the mRNA and protein expression levels of HEXA and HEXB were significantly upregulated in GBM patient samples. The results from single-cell RNA-sequencing (scRNA-seq) database and double immunostaining showed that HEXA and HEXB were specifically expressed in microglia in GBM patient samples. Furthermore, our in vitro experiments revealed that conditioned media from HEXA and HEXB knockdown-microglia cells could inhibit the proliferation and migration of GBM cells. Finally, according to survival analysis based on online database, higher expression of HEXA and HEXB was associated with poor prognosis in GBM patients. In conclusion, these results suggest that microglial HEXA and HEXB play fundamental role in GBM progression, and they will be potential biomarkers for GBM.